IT governance and management in public entities (2017)
The objective of this paper is to present the results of the study on the status and scope of IT governance and management in the public entities of the city of Manizales in the department of Caldas, Colombia. An evaluation was conducted by means of a survey, which was applied to 19 public entities. The research was developed from an inductive perspective and through a descriptive, exploratory and correlational type of study. It is concluded that the IT governance is a reality for a small portion of these entities. It is expected that the results obtained will allow to develop joint plans between public universities and entities to generate further development of its IT governance and management.